Strenuous objective life circumstances and subjective responses: perceptions of well-being when living in poverty and precarious prosperity in Romania. - Precupețu, Iuliana (Calitatea Vieții, 2016)
The purpose of this paper is to analyse the subjective well-being of two socio-structural groups (the poor and the precarious prosperous), in comparison to the group living in secure prosperity. We look at these groups trying to depict the living circumstances of these categories as filtered by their personal standards, while highlighting how these groups fare compared to each other. This endeavor is theoretically underpinned in the subjective well-being literature, in order to define subjective well-being and focuses on the relationship between objective living conditions and subjective well-being outcomes, in the attempt to disentangle the mechanisms that govern individuals’ subjective responses to objective realities. The data come from the European Quality of Life Survey on Romania carried out in this country in 2011. The analysis is done with the help of ANOVA and OLS regression. The results show overall similar low levels of subjective well-being for people living in poverty and those in precarious prosperity in comparison to the individuals in secure prosperity. For both groups under scrutiny here, analysis across life domains revealed problematic spheres along with more positive realms of life, subjective data reflecting the interplay between objective strenuous conditions and subjective mechanisms like social comparisons or adaptation.